KEMAMPUAN INTELEKTUAL, KEDISIPLINAN, MOTIVASI, DAN PENGAWASAN TERHADAP PROFESIONALISME GURU SEKOLAH MENENGAH KEJURUAN DI KOTA SURAKARTA - Rini Udayanti; Istiatin Istiatin; Bambang Mursito (ITB AAS INDONESIA Surakarta, 2020)
The research purpose was determined the effect of intellectual ability, discipline, supervision, and motivation on the vocational high school teachers’ professionalism in the Surakarta City. The research type is explanatory research. The research population are teachers of Vocational High School in Surakarta City. Sampling technique was used purposive sampling technique. Technique of data collection was used questionnaires. Data analysis techniques were used statistical analysis including of multiple linear tests, F-test, and t-test. The research results showed that 1) intellectual ability, discipline, supervision, and work motivation are simultaneously have a significant effect on the vocational high school teachers’ professionalism in Surakarta City. 2) Intellectual abilities has significant effect on the vocational high school teachers’ professionalism in Surakarta City. 3) Discipline has a significant effect on vocational high school teachers’ professionalism in the Surakarta city. 4) Work motivation has significant effect on the vocational high school teachers’ professionalism in Surakarta City. 5) Supervision has significant effect on the vocational high school teachers’ professionalism in Surakarta. Keywords: intellectual ability, discipline, supervision, work motivation, professionalism